A Comparative Between S-Commerce and M-Commerce - Castillo-Ledesma, Franklin (2023)
The internet has contributed with the development of various economic sectors, one of the most important is the sale of products and services. This research aims to present two types of sales, that can be done online and through the use of social media, which can favor businesses in their growth. The objective of this work is to carry out an analysis of the sales that are made through social media and those made through a mobile application. The development of the mobile application was produced using Android Studio with its Kotlin language in conjunction with the MySql database manager. The methodology has been of a qualitative type, with data obtained through surveys carried out with the clients of the business that were the object of the initial study. Considerable results could be obtained in social media, since its development is easier and less expensive than developing your own mobile application for the business. Finally, surveys were carried out on the participating people to measure the level of acceptance of the tools used in the commercialization of the products, in results a summary of the acceptance per question is shown, with an average acceptance of 3.16/ 5 for the mobile application and 4.5/5 for the social network used to sell the products.